2008
DOI: 10.1021/jp066448p
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid QM/MM Investigations into the Structure and Properties of Oxygen-Donating Species in TS-1

Abstract: The active oxidizing species in the H2O2/TS-1 catalytic system is investigated using a hybrid quantum mechanical/molecular mechanical approach. In this computational technique, the site of interest is described with the density functional theory using the BB1K exchange and correlation functional, and the remainder of the system is treated with a valence force field. We have examined the formation of dioxygen adsorbate structures with η and η Ti-peroxo configurations, including radical species, which arise from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…In our previous work, we showed that an appropriate QM region includes atoms up to the fifth nearest neighbour (the third oxygen atom) from the central T-site. 30,31 For the QM calculations, the terminal oxygens at the edge of the QM region are saturated with ''link'' hydrogen atoms to ensure correct electronic structure for the terminal oxygens. The terminal ''link'' atoms do not inadvertently affect the electronic solution of the overall QM calculations as an additional bond-dipole correction is added at the bond bridging the QM and MM boundary, which ensures an accurate local electrostatic potential.…”
Section: Qm/mm Simulationsmentioning
confidence: 99%
“…In our previous work, we showed that an appropriate QM region includes atoms up to the fifth nearest neighbour (the third oxygen atom) from the central T-site. 30,31 For the QM calculations, the terminal oxygens at the edge of the QM region are saturated with ''link'' hydrogen atoms to ensure correct electronic structure for the terminal oxygens. The terminal ''link'' atoms do not inadvertently affect the electronic solution of the overall QM calculations as an additional bond-dipole correction is added at the bond bridging the QM and MM boundary, which ensures an accurate local electrostatic potential.…”
Section: Qm/mm Simulationsmentioning
confidence: 99%
“…(II)). The reversible opening of a second Ti-OSi bond that would favour the inert Ti(η 2 O 2 ) peroxide, albeit feasible, is regarded to be restrained by the crystalline lattice [4]. It is possible that a certain amount of Ti is in the form of Ti(η 2 O 2 ), but theoretical studies and the acidity devel oped by TS 1 on chemisorption of hydrogen peroxide are against a major formation of it.…”
Section: The Nature Of the Active Speciesmentioning
confidence: 99%
“…By considering the site reactivity towards H2O2 in anhydrous and hydrous conditions, (To et al, 2008) confirmed the close competition between η 1 and η 2 complexes as candidates for the oxygen donating species in TS-1. Curiously, from electron paramagnetic resonance (EPR) studies, a much higher energy (by ca.…”
Section: Coordination Of Metal Centresmentioning
confidence: 58%
“…400-450 kJ mol -1 ) superoxide radical species had been reported to emerge as a result of interaction of aqueous H2O2 and non-aqueous urea H2O2 (Shetti et al, 2003). By calculating the related spectroscopic signature, (To et al, 2008) unambiguously identified the superoxide supported on tripodal Ti as the Table 4, where the calculated components of the g tensor are compared to experimental values, which are expected to be accurate to at least the third decimal place), which allowed them to argue in support of the tetrahedral site inversion mechanism as essential for promoting the catalytic activity of these systems. In the absence of definitive structural experimental characterisation, this combination of spectroscopic evidence and supporting computational results is key to unravelling the mechanisms of catalysis in atomistic and electronic detail (for more examples of such combinations see Chapters 9, 19, 21 of this volume).…”
Section: Coordination Of Metal Centresmentioning
confidence: 99%